Interim analysis of Acute Myeloid Leukaemia treated on the Red Cross Children's Hospital Rx 2071 (adapted from the MRC AML 15 protocol) - Thomas, Karla Mari (Department of Paediatrics and Child Health, 2018)
Background: Due to the poor outcomes achieved in acute myeloid leukaemia (AML) treatment, the Red Cross War Memorial Children's Hospital (RCWMCH) Oncology service changed from a BFM-87 based protocol to one based on MRC-AML15 in 2007. Rationale: This study was designed to assess the outcomes and treatment - related toxicity among children treated with RCWMCH protocol Rx 2071. Methods: This was a retrospective review of AML patients treated with Rx2071 between 2007 and 2012 at RCWMCH. Patients with acute promyelocytic leukaemia (APL) and Down Syndrome were excluded. Risk was assigned by cytogenetics. Good risk patients were those with t(8;21), t(16,16) and inv(16). Poor and standard risk included all other cytogenetics according to MRC-AML15. Data pertaining to toxicity was obtained from patient folders. Results: Thirty five children were treated on Rx 2071 during the study period. Males comprised 51.4% (18/35) and females 48.6% (17/35). Age at diagnosis ranged from 0.33 to 12.51 years with the median being 5.68 years. Follow-up from remission in the patients who survived ranged from 1 year 10 months to 9 years 1 month with a median of 62.5 months. Fifteen patients had favourable cytogenetics. Event free survival (EFS) for the good risk group was 85.6%. Twenty patients presented with standard/poor risk cytogenetics. Five patients were deemed poor risk with one having major karyotype abnormalities and four not achieving remission. The remaining fifteen were deemed standard risk by cytogenetics. EFS in this group was 32.4%. Two standard/poor risk patients were transplanted in first complete remission (CR1) and two patients were transplanted in second complete remission. (CR2) Patients had a median of four neutropaenic fevers, and required a median of eight packed cell and eleven platelet transfusions. There were 39 positive blood cultures. There were no chemotherapy related deaths. Discussion: The EFS for good risk patients is excellent but the EFS for standard/poor risk group is not on par with results being achieved in high income countries. The toxicity is not excessive on Rx2071. The results achieved on this protocol were superior to that of the previous BFM- based protocol. Conclusion: The results of this study support the continued use of Rx2071 at RCWMCH.